考察一般项:n(n+1)/2=n²/2 +n/2
n
∑ n(n+1)/2=(1/2)(1²+2²+...+n²)+(1/2)(1+2+...+n)
n=1
=n(n+1)(2n+1)/12 +n(n+1)/4
=[n(n+1)/12][(2n+1)+3]
=[n(n+1)/12](2n+4)
=n(n+1)(n+2)/6
提示:很简单,就是利用两个求和公式1²+2²+...+n²=n(n+1)(2n+1)/6和1+2+...+n=n(n+1)/2。
∑n(n+1)/2 应该是∑2/n(n+1)否则不存在
如果是这样:
∑2/n(n+1)
=2∑1/n(n+1)
=2【1/1×2+1/2×3+。。。。+1/n(n+1)+......】
=2[1-1/2+1/2-1/3+1/3-1/4+....+1/n-1/(n+1)+....] 内部全部抵消
所以
原式=2×1=2
前面的回答有道理,现在我们暂且当∑n(n+1)/2没有问题,那么
∑n(n+1)/2=1/2∑(n^2+n)
=1/2(∑n^2+∑n)
=1/2[n(n+1)(2n+1)/6+n(n+1)/2]
=n(n+1)(2n+4)/12
解:∑n(n+1)/2=1/2∑n(n+1)
=1/2(∑nn+∑n)=1/2(n(n+1)(2n+1)/6+n(n+1)/2)
=n(n+1)[(2n+1)/6+1/2]/2=n(n+1)(n+2)/6